Analysis of Holistic Midwifery Care For Maternal Health - Ai Nur Zannah (NHM PRESS, 2022)
Maternal health is one of the global health development indicators which is always a challenge for all countries in the world strive to improve health and reduce mortality. Health is a state of complete physical, mental, social and spiritual well-being, so that holistic care is needed to fulfill these circumstances. The purpose of this research is analyzing holistic midwifery care for maternal health. The research design used a cross-sectional quantitative study that is analyzing the relationship between physical, social, mental, and spiritual health status to the holistic health status of the mother. Sampling was carried out by purposive sampling of 51 pregnant women. The analysis used Pearson's correlation test. The research results show 54.25% of pregnant women are in a state of less than average physical health status; 52.94% have less than average social health status; 45.1% have a mental health status of symptoms of anxiety; 41.18% have less than average spiritual health status. The statistical test results show that there is a relationship between physical, social, mental and spiritual health status on the mother's health status holistically. Holistic midwifery care can be carried out starting from assessment to management of early detection and referral and evaluation to optimize health conditions, especially maternal health.